ChemInform Abstract: Hazard Property Classification of Waste According to the Recent Propositions of the EC Using Different Methods. Issue 11 (March 2015) - Hennebert, Pierre; van der Sloot, Hans A.; Rebischung, Flore; Weltens, Reinhilde; Geerts, Lieve; Hjelmar, Ole
Abstract Review: 24 refs.